Epigenetic signatures underlying inflammation: an interplay of nutrition, physical activity, metabolic diseases, and environmental factors for personalized nutrition - Ramos-Lopez, Omar; Milagro, Fermin I.; Riezu-Boj, Jose I.; Martinez, J. Alfredo (Inflammation research, 2021)
Aim and objective Emerging translational evidence suggests that epigenetic alterations (DNA methylation, miRNA expression, and histone modifications) occur after external stimuli and may contribute to exacerbated inflammation and the risk of suffering several diseases including diabetes, cardiovascular diseases, cancer, and neurological disorders. This review summarizes the current knowledge about the harmful effects of high-fat/high-sugar diets, micronutrient deficiencies (folate, manganese, and carotenoids), obesity and associated complications, bacterial/viral infections, smoking, excessive alcohol consumption, sleep deprivation, chronic stress, air pollution, and chemical exposure on inflammation through epigenetic mechanisms. Additionally, the epigenetic phenomena underlying the anti-inflammatory potential of caloric restriction, n -3 PUFA, Mediterranean diet, vitamin D, zinc, polyphenols (i.e., resveratrol, gallic acid, epicatechin, luteolin, curcumin), and the role of systematic exercise are discussed. Methods Original and review articles encompassing epigenetics and inflammation were screened from major databases (including PubMed, Medline, Science Direct, Scopus, etc.) and analyzed for the writing of the review paper. Conclusion Although caution should be exercised, research on epigenetic mechanisms is contributing to understand pathological processes involving inflammatory responses, the prediction of disease risk based on the epigenotype, as well as the putative design of therapeutic interventions targeting the epigenome.